Application of a Persistent Dissolved-phase Reactive Treatment Zone for Mitigation of Mass Discharge from Sources Located in Lower-Permeability Sediments - Marble, J.C. (Water Air Soil Pollut, 2014)
The purpose of this study is to examine the development and effectiveness of a persistent dissolved-phase treatment zone, created by injecting potassium permanganate solution, for mitigating discharge of contaminant from a source zone located in a relatively deep, low-permeability formation. A localized 1,1-dichloroethene (DCE) source zone comprising dissolved- and sorbed-phase mass is present in lower permeability strata adjacent to a sand/gravel unit in a section of the Tucson International Airport Area (TIAA) Superfund Site. The results of bench-scale studies conducted using core material collected from boreholes drilled at the site indicated that natural oxidant demand was low, which would promote permanganate persistence. The reactive zone was created by injecting a permanganate solution into multiple wells screened across the interface between the lower-permeability and higher-permeability units. The site has been monitored for nine years to characterize the spatial distribution of DCE and permanganate. Permanganate continues to persist at the site, and a substantial and sustained decrease in DCE concentrations in groundwater has occurred after the permanganate injection.. These results demonstrate successful creation of a long-term, dissolved-phase reactive-treatment zone that reduced mass discharge from the source. This project illustrates the application of in-situ chemical oxidation as a persistent dissolved-phase reactive-treatment system for lower-permeability source zones, which appears to effectively mitigate persistent mass discharge into groundwater.